KANDUNGAN KADMIUM (Cd) PADA TANAH DAN CACING TANAH DI TPAS PIYUNGAN, BANTUL DAERAH ISTIMEWA YOGYAKARTA - , Heny Mayasari SETYONINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Soil in Piyungan Controlled Landfill Municipal Waste Disposal (Piyungan TPAS, stands for Tempat Pembuangan Akhir Sampah) are sensitive with cadmium contamination that can negatively effecting human health and threating ecosystem balance. Cadmium has potency to accumulate in living thing, so soil cadmium contamination monitoring activties, directly or indirectly, are very important to do. The aims of t research were to analyze cadmium content in soil and in earthworms, to analyze cadmium pollution level in soil, to analyze cadmium content ratio in soil and in earthworms and to analyze Piyungan TPAS local communitiesâ respon to the cadmium pollution risk. The research was divided into in-sites study and laboratory analysis. The in-sites studies consisted of soil and earthworms sampling, soil environmental factors measurement and corespondents interviewed. Laboratory analysis consisted of cadmium content, organic compounds and soil textures analysis. Cadmium pollution level analyzed with Contamination-Pollution Index (Lacatusu, 1998). The results showed that cadmium content in soil were <0,01 â 0,47 ppm, it had lower content than maximum cadmium content allowed in soil. Especially for zone III and zone I sampling point 1 and 2, they had higher soil cadmium content than cadmium content standard for unpolluted soil, and for control areas, they had lower cadmium content than maximum cadmium content allowed in soil. The cadmium content in Piyungan TPAS soil were not always higher than control sites. Earthworms contained 0,35 â 0,45 ppm of cadmium and in several Piyungan TPASâs zones contained less cadmium than control sites. Cadmium pollution level were ranged from very slight contamination to very severe contamination. The active area of Piyungan TPAS had a worse cadmium contamination than other area. Cadmium ratio in soil and in earthworms were 0,13 : 1,75. Local communities who lived near Piyungan TPAS did not understand enough and awarness about cadmium pollution risk, especially cadmium bioacumulation in their place.